PENINGKATAN KINERJA KARYAWAN DITINJAU DARI DISIPLIN KERJA DAN KEPEMIMPINAN - KHAERUMAN (AKADEMIKA, 2019)
Human resources are an integral part and play a important role in an organization. In this case found a problem with the management such as lack of disipline and lack of supervision.The research method uses descriptive research methods with quantitative research, because the number of studies is 31 people, the research sample taken is 31. Because the number of samples is based on population, the saturated sampling technique is used. With technical analysis of correlation test data. This correlation test stated that the closeness of the relationship between work discipline and leadership on employee performance is very strong if the value of r> 0.5 and Multiple Linear Regression Test, with the equation: Y = 4,793 + b1 X1 + b2 X2 The results of this study have the effect of work discipline on the performance of employee employees at PD. Karya Mandiri Serang, there is an influence of leadership on the performance of employee employees at PD. Karya Mandiri Serang. The results of the simultaneous test obtained Fcount values with a real level of 5%. The value of free degree for numerator was greater than Ftable (16,802> 3,33) and Sig F was smaller than α (0,000 <0,05) so that there was a significant effect between work discipline and leadership on the performance of employee employees at PD. Karya Mandiri Serang. Based on the research data, it is stated that there are influences of work discipline and leadership on the performance of employee employees at PD. Karya Mandiri Serang